2004
DOI: 10.1051/forest:2004068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silviculture treatments on vegetation after fire in Pinus halepensis Mill. woodlands (SE Spain)

Abstract: -In August 1994, two great fires occurred in SE Spain burning 44 000 ha of mature Pinus halepensis Mill. forests. Experimental silviculture treatments were carried out on five-year-old P. halepensis seedlings from natural regeneration: thinning to a final density of 1 600 trees/ha, total scrubbing, thinning plus scrubbing, thinning plus pruning to half the total height, scrubbing plus pruning and thinning, scrubbing plus pruning. Treatments were carried out in 45 permanent plots located in two localities with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…Background studies demonstrated the same conclusions [21,44] in other Mediterranean areas. Thus, site quality seems to play an important role in seed production, which is linked to tree density, and in turn influences seed number [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Background studies demonstrated the same conclusions [21,44] in other Mediterranean areas. Thus, site quality seems to play an important role in seed production, which is linked to tree density, and in turn influences seed number [13].…”
Section: Discussionmentioning
confidence: 99%
“…If a new fire occurred before the tree reached the reproductive phase, post-fire natural regeneration might be deficient [10,43] which produces important environmental impacts as risk of soil loss, loss of biodiversity, loss of carbon sink, etc. This information could be very useful for foresters when making management decisions, for example in applying silvicultural treatments in the early stages of regrowth [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is known that P. bituminosa, which is very common during the first years after fires (Martínez-Sánchez and Herranz 1999; De las Heras et al 2004) and R. peregrina (both positively correlated with the abundance of rabbits), are commonly favoured by other herbivores due to their high nutritive value (Chapuis et al 1995;Bartolomé et al 1998;Sternberg et al 2000;Ventura et al 2000;Sternberg et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Observed rabbit colonisation and the increase in rabbit abundance in burnt areas could be related to the appearance of open habitats with a significant surface area occupied by bare ground and a high diversity of low herbaceous, mostly gramineous and leguminous vegetation (Martínez-Sánchez and Herranz 1999; De las Heras et al 2004), which coincides with known habitat preferences for rabbits (Fa et al 1999;Beja et al 2007;Ferreira and Alves 2009). Our study shows an increase in rabbit abundance for at least 5 years after the fire indicating that in the mid-term, forest fires have a relatively positive effect on rabbit abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning can be performed with a clearing saw (portable swinging arm scythe) since the more expensive use of the chain-saw is still not needed. Although effects of silvicultural treatments on pine growth [13] and on the accompanying vegetation [6] two years after treatments have been studied, effects of silvicultural treatments on the first stage of cone and seed production are currently not well known. In this sense [13] points out that silvicultural treatments including thinning improved the probability of cone production by a factor of 2.07 in relation to the control 22 months after treatment.…”
Section: Introductionmentioning
confidence: 99%